A Review of Studies Evaluating Insecticide Barrier Treatments for Mosquito Control From 1944 to 2018. (June 2019) - Stoops, Craig A; Qualls, Whitney A; Nguyen, Thuy-Vi T; Richards, Stephanie L
Background and Purpose: Barrier insecticide treatments have a long history in mosquito control programs but have been used more frequently in the United States in recent years for control of invasive "backyard" species (eg, Aedes albopictus ) and increases in incidence of vector-borne diseases (eg, Zika). Methods: We reviewed the published literature for studies investigating barrier treatments for mosquito control during the last 74 years (1944-2018). We searched databases such as PubMed, Web of Science, and Google Scholar to retrieve worldwide literature on barrier treatments. Results: Forty-four studies that evaluated 20 active ingredients (AIs) and 21 formulated products against multiple mosquito species are included. Insecticides investigated for efficacy included organochlorines (dichlorodiphenyltrichloroethane [DDT], β-hexachlorocyclohexane [BHC]), organophosphates (malathion), and pyrethroids (bifenthrin, deltamethrin, permethrin, lambda-cyhalothrin) as AIs. Study design varied with multiple methods used to evaluate effectiveness of barrier treatments. Barrier treatments were effective at lowering mosquito populations although there was variation between studies and for different mosquito species. Factors other than AI, such as exposure to rainfall and application equipment used, also influenced control efficacy. Conclusions: Many of the basic questions on the effectiveness of barrier insecticide applications have been answered, but several important details still must be investigated to improve precision and impact on vector-borne pathogen transmission. Recommendations are made to assist future evaluations of barrier treatments for mosquito control and to limit the potential development of insecticide resistance.